Hypertension as a prominent manifestation secondary to renal artery lesions in pediatric Behcet's disease - Xinning Wang; Zhixuan Zhou; Jianguo Li; Gaixiu Su; Xiaohui Li (BMC, 2024)
Abstract Objective Hypertension caused by vascular Behcet's disease (BD) is an important prognostic factor of paediatric BD. However, much less is known about its clinical features. The objective of this study was to investigate the clinical characteristics of paediatric vascular BD complicated by hypertension. Methods A retrospective study was carried out in paediatric BD patients complicated by hypertension treated in the Children's Hospital Capital Institute of Paediatrics from Jan 2009 to Dec 2022. Results Of 65 BD patients, 6 (9.2%) were complicated by hypertension, 5 patients were female, and the median ages of onset and diagnosis were 9.8 years and 11.3 years, respectively. Three patients were found to have cardiac involvement and hypertensive retinopathy secondary to hypertension. Five of the 6 patients with hypertension had right renal artery involvement, and all of them were treated with glucocorticoids and immunosuppressants. Four patients were treated with biological agents. One patient with severe renal artery stenosis underwent unsuccessful vascular interventional therapy. After 3-6 years of follow-up, five patients were found to have renal atrophy, and one patient was at stable condition. Conclusion Hypertension in paediatric BD is mainly caused by renal artery involvement. Early recognition and treatment of vascular involvement in BD is important to prevent poor prognosis.